LITERARY FAIRY TALE AS A MEANS OF FORMING THE TOLERANCE IN PRIMARY SCHOOL CHILDREN - Derkachova, Olga; Tytun, Oksana (Mountain School of Ukrainian Carpaty, 2023)
The article deals with the study of the pedagogical potential of a literary fairy tale as a means of forming tolerance in primary school children. As illustrative material, the authors use LGBT fairy tales that actually reflect the topics that previously considered taboo. The aim of the research is to analyze modern queer tales considering social and literary tendencies, to determine the thematic section and to investigate the peculiarities of character creating process, as well as to generalize and systematize the literary experience of queer texts and trace how such fairy tales help to form a tolerant attitude towards others. The object of research is modern queer tales, which have become significant in culture and have caused mixed reaction. The research methodology involves historical-comparative, existential, hermeneutic and culturological methods. In postmodern world, there are significant changes in a person’s awareness of his/her place in the family and among people, there is also a search for self-identification and understanding of what is moral or immoral. The changes in social, value, and morality are reflected in fiction, which captures “possible – impossible”, “right – wrong”, “bad – good” at certain stages of development of the society. The appearance of queer literature and discussions around them testify to the readiness of the society for dialogue and understanding that the world is beautiful in its diversity. A person with his/her qualities, values, uniqueness and desire to be useful to the society in queer tales occupies an important place. Equally important is the issue of freedom to choose a life path, life purpose, a partner, as well as the right to self-expression. The origin and development of the issue is researched, the first LGBT books for children are briefly analyzed, and the most recent and most popular tales are focused on. Among them are “King and King” by Linda De Haan and Stern Nijland (2002), “The bravest Knight that Ever Lived” by Daniel Errico (2014), “The Princes and the Treasure” by Jeffrey A. Miles (2014), “Princess Princess Ever After” by Katie O’Neill (2016). The narrative features of these tales are elucidated, a comparative analysis of the folklore tale and a new literary one is carried out. The structural matrix of the queer tale has been determined as a traditional one: tasks, hero and helper, journey, initiation, magic objects and happy end. Attention is focused on the characteristics of queer characters: their traits, actions, relationship with people. The problems and the leading motives of the tales are identified, and it is emphasized that the purpose of such literature is to show the world in its diversity, where there is a place for everyone. It is also advisable to focus on the deeds and actions of the characters but not on their sexual preferences.